Postoperative (Pressure) Alopecia on Head Rest Fixation Pointes Area, Following Intracranial Removal of Meningioma. A Rare but Disturbing Complication to Consider. - Chakdoufi , Sanae; Mamoune, El Mostarchid; Brahim, El Mostarchid; Anas, Guerboub Ahmed (Jour Med Resh and Health Sci, 2023)
Postoperative (pressure) alopecia (PPA) is a very rare complication, well known by cardiologic surgeons and plasticiens. PPA localized in head rest fixation pointes is exceptionally reported by neurosurgeons. To report a case of PPA localized at head rest fixation pointes. A 50-year-old man presented a PPA occipital localized head rest fixation pointes one month postoperatively following intracranial removal of anterior fosse meningioma. This alopecia disappears spontaneously and totally three month ago. The mechanism of this PPA is discussed. This complication must be considered in postoperative follow-up if intracranial surgery with expected blood loses and lengthy surgery.